2017
DOI: 10.1371/journal.pone.0174396
|View full text |Cite
|
Sign up to set email alerts
|

Defective bone repair in mast cell-deficient Cpa3Cre/+ mice

Abstract: In the adult skeleton, cells of the immune system interact with those of the skeleton during all phases of bone repair to influence the outcome. Mast cells are immune cells best known for their pathologic role in allergy, and may be involved in chronic inflammatory and fibrotic disorders. Potential roles for mast cells in tissue homeostasis, vascularization and repair remain enigmatic. Previous studies in combined mast cell- and Kit-deficient KitW-sh/W-sh mice (KitW-sh) implicated mast cells in bone repair but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 37 publications
1
35
2
Order By: Relevance
“…The results of our study are in contrast to a study investigating bone repair in another c‐Kit ‐independent mouse model of MC deficiency . In this study, bone formation rather than bone resorption was disturbed in the absence of MCs.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of our study are in contrast to a study investigating bone repair in another c‐Kit ‐independent mouse model of MC deficiency . In this study, bone formation rather than bone resorption was disturbed in the absence of MCs.…”
Section: Discussioncontrasting
confidence: 99%
“…Osteoclast numbers were only temporarily decreased. The authors suggested that MCs might have a positive impact on bone repair that is mediated by increased revascularization . In contrast, we actually found a slight increase of the bone fraction in the callus of Mcpt5‐Cre R‐DTA mice on day 7, suggesting that repair might have started slightly earlier because of the overall reduced inflammation in the absence of MCs.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Investigations of bone repair in a cortical window defect in a c-Kit-independent Cpa3 Cre/+ mouse model found impaired bone regeneration, as confirmed by reduced cortical bridging, vascularization, and bone mineralization. The authors further observed diminished osteoclast activity at earlier stages, but increased osteoclast activity in the late healing phase (204). Therefore, MC functions in bone repair may comprise blood vessel formation as well as anabolic and catabolic processes during fracture repair and remodeling (Figure 1D).…”
Section: Bone Fracture Healingmentioning
confidence: 84%